Faith-Based Response to COVID-19 Pandemic: Assessing the Pastoral Response to Mitigation and Suppression - Ilo, Stan Chu (Concilium, 2024)
This research discusses the communication strategies adopted by two parish-based COVID-19 task forces in a US Catholic diocese in order to keep their parishioners safe. Through an ethnographic study, the research shows how these faith-based religious leaders developed the mitigation and suppression measures against COVID-19 for their parishioners between March 2020-March 2021 during and after the lockdown period. The research reports on the social marketing tools adopted by these task forces. Through a reflective analysis on the themes discovered through interviews with these faith-based leaders, the research demonstrates how faith-based actors can effectively play an important role in health education during an outbreak of a highly contagious novel infection like the COVID-19 virus.